Hubungan Antara Persepsi Remaja Terhadap Komunikasi Orangtua-Remaja Dengan Kenakalan Remaja - Halimatus Sa’diah (IAI Darussalam, 2016)
This study aims to determine whether there is a relationship between adolescent perception of the parent-teen communication with juvenile delinquency. These research subjects totaling 283 adolescents aged 15-18 years who attend school at SMK X Surabaya. Collecting data in this study using a survey method, consisting of a measuring tool adolescent perception of the parent-teenager communication as much as 34 eggs and juvenile delinquency measuring instrument consisting of 26 items compiled by the researcher. Analysis of the data used is non-parametric statistical techniques Spearman's Rho correlation test with SPSS 16 for windows. Results of analysis of experimental data showed the value of the variable correlation between adolescent perception of the parent-teenager communication with juvenile delinquency of -0.362 with probability value 0,000. This shows that there is a significant negative correlation between adolescent perception of the parent-teen communication with juvenile delinquency